Antiphospholipid syndrome: a case report - Moreira, Lisa Teresa (2017)
Introduction: Antiphospholipid syndrome is an autoimmune disorder that increases the risk of thrombosis. It has multiple clinical manifestations, making the diagnosis a challenge. Case report: A 25 year-old Caucasian woman presented with right frontal headache, radiating to the eyes, with loss of sensation on the right side of the face and flattening of the right naso-labial fold. Computerized tomography of the head did not reveal acute alterations. Loss of sensation on the right side of the body appeared after 48 hours. Computerized tomography revealed thrombosis of the anterior and medial third of superior longitudinal sinus. Further investigation revealed the presence of lupus anticoagulant, antinuclear antibodies (titers of 1/320), and anti-β2-glycoprotein antibodies confirming the diagnosis of antiphospholipid syndrome. Comment: Stroke is the first manifestation of the antiphospholipid syndrome in 13.5% to 15% of cases, preferentially affecting the middle cerebral artery. Sinus thrombosis is a rare presentation associated with non-specific symptoms. Early diagnosis of stroke in young people remains difficult. Health providers need to be aware of this syndrome with the increase in risk factors such as obesity among the young.